Biodegradable Polymers for Sustainable Engineering Applications - Bhatti, Sikandar Ali (J-STAR: Journal of Social & Technological Advanced Research, 2025)
The biodegradable polymers are currently gaining special importance as an essential material in the field of sustainable engineering, due to their possibility of being degraded by the natural environment as environmentally friendly products. These polymers are a good alternative to traditional plastics made of petroleum, which causes a significant contribution to ecological pollution of the environment and harm on the ecosystem on the long term. This research paper will discuss properties, synthesis, degradation, engineering uses and performance of biodegradable polymers in the environment. The method of systematic review and qualitative synthesis was selected in order to evaluate the condition of the existing research and identify challenges and opportunities to adopt this research in the industry. Results show that though polymers like polylactic acid (PLA) and polyhydroxyalkanoates (PHAs) are high in their mechanical performance and biodegradability there are still hurdles implicitly like high cost of production, inconsistent rate of degradation and lack of large scale infrastructure. The paper concludes that biodegradable polymers have the potential to be of great use in sustainable engineering through interdisciplinary innovation, industrial scale adoption and proper dumping techniques.